Market Price Distortions in Islamic Microeconomics - M. Riyan Dirgantara; M. Ilham Sembiring; Reza Fahlevy; Rizqa Amelia (Sufiya Journal of Islamic Studies, 2023)
This article discusses price distortions in the market caused by the hoarding of diesel fuel in Medan. Price distortions occur when there are disruptions in the market mechanism that result in prices that are not proportional to the actual supply and demand. Several factors that contribute to price distortions in the hoarding of diesel fuel include limited supply conditions, the presence of middlemen or boarders, price speculation, and policy uncertainty. The impact of these price distortions can include price disproportionate increases, operational disruptions for businesses, and economic inequality. This article utilizes a qualitative descriptive method with a literature research approach. Qualitative research methods are used to obtain findings that cannot be obtained through quantitative methods, while the literature research approach utilizes library resources to gather research data. To address price distortions caused by the hoarding of diesel fuel, several steps can be taken, including strict monitoring and law enforcement, stabilizing the supply of diesel fuel, public education and awareness, price transparency, and referring to reliable sources for more detail and updates -to date information.